Fungsi Dinas Kebersihan dan Ruang Terbuka Hijau Sebagai Komunikator dalam Membangun Destination Branding Kampung Wisata Genteng Candirejo di Surabaya - Permana, Anggriyan; Sumarah, Noorshanti; Romadhan, Mohammad Insan (Universitas 17 Agustus 1945 Surabaya, 2020)
Abstract The Sanitation and Green Open Space Department as a communicator, through the Community Empowerment Sub-Division, conveyed a message to the community with one of its messages, namely to build a branding destination in the tourist village of Genteng Candirejo. Interestingly, DKRTH does not have a public relations position in its organizational structure, which makes researchers interested in knowing the DKRTH's function as a communicator in building the destination branding of the Candirejo Tile Tourism Village in Surabaya. This study uses the concept of destination brand social image patterns in the study of tourism communication as a discussion analysis knife. This research resulted in a conclusion as a DKRTH communicator trying to give an impression to the public by becoming a facilitator of communication, media relations and program assistance so that the social image of the village destination branding is getting stronger Keywords : DKRTH Function, Public Relations Activities, Destination Brand Social Image Pattern